Transformasi Limbah Menjadi Berkah: Analisis Proses Produksi Daur Ulang Limbah Kreatif Berseri Dalam Perspektif Ekonomi Islam - Septi Tri Dinanti; Nilda Susilawati; Yunida Een Fryanti (CV. ITTC INDONESIA, 2026)
Waste management problems in Indonesia, particularly in Bengkulu City, continue to increase and cause environmental, health, and social impacts. Amid the limitations of conventional waste management, Limbah Kreatif Berseri Waste Bank emerges as a community-based initiative that transforms waste into economically valuable products. However, production activities located near residential areas and places of worship raise issues related to social impact and potential harm. This study aims to analyze the production process of Limbah Kreatif Berseri from an Islamic economic perspective, identify the constraints faced in the production process, and examine efforts to enhance public trust in recycled products. The research employs a descriptive qualitative method using data collection techniques such as observation, interviews, and documentation. The findings indicate that the production process generally aligns with Islamic economic principles, including tauhid (monotheism), justice, humanity, and maslahah (public benefit). Nevertheless, several technical and environmental challenges remain. To address these issues, the enterprise undertakes community empowerment, improves product quality, and strengthens social engagement to realize sustainable waste transformation into economic and social benefits.